FRI0435 Clinicopathological correlation in inflammatory myositis: analysis of the remicam cohort (REGISTRY OF INFLAMMATORY MYOSITYS FROM MADRID, SPAIN). (12th June 2018) - Joven, B.E.; Lozano, F.; Nuño, L.; López-Longo, F.J.; Toldos, O.; Rabadán, E.; Hernández, A.; Martínez-Barrios, J.; Larena, C.; Blazquez, M.; Barbadillo, C.; Llorente, I.; et al.
Abstract : Background: Associations between muscle pathology and clinical features in inflammatory myositis(IM) are not well defined Objectives: to describe the pathological findings in REMICAM 1 muscle biopsies, and analyse their associations with clinical features Methods: All patients with available biopsy were included. According to the score proposed by ENMC workshop 2, from muscle biopsy reports was extracted: inflammatory cells and location (endomysial, perimysial, perivascular), rimmed vacuola, fibre atrophy, necrosis, regeneration, and HLA expression. Descriptive analysis and association studies between histology and clinical features were performed (t and chi square tests, univariate logistic regression with OR) Results: From 479 patients, 244 (51%) had available biopsy. Most frequent findings were: inflammatory infiltrates(75%): endomysial(44%), perimysial(49%) perivascular(26%); fibre atrophy(54%), perifascicular(27%); necrosis(55%) and regeneration(47%). HLA expression was +in 60/75 cases(80%). Endomysial infiltrate was associated with PM (OR 0.4;p<0.0001), cardiac involvement (OR 2.2;p=0.014), less arthritis (OR 0, 5;p=0.01) and older age (51 vs 42 y;p<0.01); perimysial infiltrate and perifascicular atrophy with DM (OR 3.8;p<0.0001) and younger age (40 vs 48 y;p<0.05); necrosis with cardiac involvement (OR 2.1;p=0.035), neoplasia (OR 2.5;p=0.02) and no connective tissue disease (OR 0.4;p=0.01); and HLA with PM (OR 0.1;p=0.003) Conclusions: most frequent histologic findings in IM muscle are inflammatory infiltrates, necrosis, HLA expression and perifascicular atrophy. Endomysial infiltration and HLA are characteristic of PM, and perimysial infiltration/perifascicular atrophy of DM. Endomysial infiltrates are associated with cardiac involvement. Necrosis is more frequent in neoplasia and less in connective tissue diseases, and is associated with cardiac involvement and older age. Our data suggest that muscle biopsy might help to identify those IM patients at higher risk of severe complications, as neoplasia or cardiac involvement References: [1] Nuño L. Rheumatol Clin2017. [2] De Bleecker JL. Neuromuscular Disorders2015. Disclosure of Interest: None declared